Analysis of the Influence of Work Discipline, Leadership Style, and Service at the Village Hall Office on the Level of Community Satisfaction - Nike Nanda Pratiwi; Nurul Badriyah; Evi Fitrotun (Jurnal Price : Ekonomi dan Akuntasi, 2024)
This study aims to analyze the influence of work discipline, leadership style, and service on the level of community satisfaction at the Slaharwotan Village Hall Office, Ngimbang District, Lamongan Regency. Community satisfaction is an important measure in the implementation of public services because it reflects the conformity between public expectations and the performance of services received. This study uses a quantitative approach with the population of the Slaharwotan Village community and a sample of 99 respondents. Data were collected through a questionnaire based on the Likert scale, then analyzed using validity, reliability, classical assumption, multiple linear regression, t-test, F-test, and determination coefficient with the help of SPSS. The results of the study showed that work discipline had a positive and significant effect on community satisfaction with a t-value of 6.605 and a significance of 0.000. Leadership style had a positive and significant effect with a t-value of 3.066 and a significance of 0.003. Services also had a positive and significant effect with a t-value of 2.829 and a significance of 0.006. Simultaneously, the three variables had a significant effect on community satisfaction with an F value of 42.897 and a significance of 0.000. The R Square value of 0.575 indicates that 57.5% of the variation in community satisfaction can be explained by work discipline, leadership style, and service. The dominant variable is work discipline because it has the highest standard regression coefficient and beta values.